THE INFLUENCE OF LOCATION ACCESSIBILITY ON PURCHASE DECISION WITH SERVICE QUALITY AS AN INTERVENING VARIABLE (Case Study on Warung Bebek Pak Wito Tebing Tinggi Customers) - Mohd Heikal; Harley Agustian; Iqbal Fauzi Pakpahan (Universitas Efarina, 2023)
In this study, the population was Warung Bebek Pak Wito Tebing Tinggi customers, namely 60 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population, totaling 60 customers of Warung Bebek Pak Wito Tebing Tinggi, will be used as the research sample. the first hypothesis is accepted, meaning that Location Accessibility (X) has a positive and significant effect on Service Quality (Y1). the second hypothesis is rejected, meaning that Location Accessibility (X) has a significant effect on Purchase Decision (Y2). the third hypothesis is accepted, meaning that Service Quality (Y1) has a positive and significant effect on Purchase Decision (Y2).